Determinants of Resilience Adolescent for Not Doing Premarital Sexual Intercourse (Data Analysis of Integrated Biologic and Behavior Survey, 2013) - Rizky Setiadi; Popy Yuniar; Besral Besral; Umi Kalsum (Humanistic Network for Science and Technology (HNST), 2018)
The adolescent is a transition period from childhood to adulthood, signed by rapid development in physical, mental, emotional and social. Earlier sexual initiation by the adolescent, increasing the risk to get sexually transmitted diseases, unmeet need, teen's pregnancies, and unsafe abortion. The younger adolescent sexual intercourse, the greater the risk of transmission of infectious diseases through sexual transmission. In Indonesia, the age of adolescent who had premarital sexual intercourse was 9-24 years old. Prevalence of unmarried boys who had to have sex is 8.3% and girls are 1%. This study aims to know the determinants of resilience adolescent for not doing premarital sexual intercourse. The results show that adolescent's survival cumulative proportion is about 92.6% and age mean of sexual debut is 15.8 years old. Factors associated with adolescent's survival not to have premarital sexual intercourse are sexual arousal behavior (AHR: 7.7; 95% CI: 5.2-11.3), drunk with alcohol (AHR: 1.5; 95% CI: 1.1-2) and kissing. The association between kissing and adolescent's survival rate is different in each time unit (year). Need enforcement to give earlier education about adolescent's health reproduction, not just as formal education in high school, but also in the family and adolescent's community to prevent premarital sexual intercourse among adolescents. Keywords: Premarital sexual intercourse, Adolescent’s survival